A rare diagnosis has no certainty, but still they occur: A case report - Marthandan, Megha; Geetha, Nithya; Joseph, Susy; AS, Ajithkrishnan; Kiran, N (Indian Journal of Case Reports, 2024)
Pain and swelling are among the most frequently encountered complaints in an orthopedics outpatient department (OPD) relatively less common in a pediatric OPD. A high level of suspicion is required to diagnose bone diseases. Common conditions such as rickets, septic arthritis, and tuberculosis must be ruled out. Treatment such as antibiotics, anti-inflammatory drugs, or steroids may mask an underlying serious condition in which if left untreated can cause significant morbidity and mortality to the person. Here, we discuss a case of a young infant 11 months of age who had symptoms suggestive of septic arthritis and was later found to have Brodie’s abscess which is a type of subacute osteomyelitis on further evaluation which is usually mistaken as a tumor. This age at presentation is rare.